Solid electrolyte, battery containing solid electrolyte and preparation method of solid electrolyte

By using materials such as cellulose and polymer monomers in lithium batteries for in-situ polymerization, a solid electrolyte-separator composite with high thermal stability is formed, which solves the problems of poor hygroscopicity of the separator materials of lithium batteries and insufficient electrolyte wetting, and improves the problem of lithium battery separator materials, which is a good choice for the in-situ polymerization of the electrolyte. The thermal runaway safety and electrical performance of lithium batteries, while reducing costs.

CN119181849AInactive Publication Date: 2024-12-24WANXIANG 123 CO LTD

Patent Information

Application Number
CN202411270232.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The separator materials of existing lithium batteries have problems such as poor hygroscopicity and insufficient electrolyte wetting, resulting in high heat shrinkage and increased battery impedance, affecting the safety and energy density of lithium batteries.

Method used

Solid electrolytes prepared by thermally in-situ polymerization process by thermally initiating in situ polymerization process are used to form a high thermal stability membrane-electrolyte composite to improve the heat resistance and wetting of the membrane. while reducing battery costs.

Benefits of technology

Without increasing the thickness of the membrane, the thermal runaway safety and electrical properties of lithium batteries are significantly improved, the material and processing costs are reduced, and solid electrolyte-diaphragm composites with high mechanical strength and high thermal stability are formed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005038486750000061
    Figure BDA0005038486750000061
  • Figure BDA0005038486750000071
    Figure BDA0005038486750000071
  • Figure BDA0005038486750000081
    Figure BDA0005038486750000081
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a solid electrolyte, a battery containing the solid electrolyte and a preparation method of the solid electrolyte. Wherein the solid electrolyte is prepared from an electrolyte precursor through a thermally initiated in-situ polymerization process; the electrolyte precursor comprises cellulose, a polymer monomer, a lithium salt, a plasticizer, an additive and a thermal initiator; according to the invention, cellulose is dissolved in a solid electrolyte precursor and is uniformly compounded with the diaphragm during in-situ polymerization, so that the thermal shrinkage resistance of the diaphragm and the overall safety of the battery are improved; compared with a process for improving the safety by using cellulose on the diaphragm side, the method has the advantages that the diaphragm does not need to be subjected to any additional treatment, the thickness of the diaphragm is not increased, and the prepared battery is good in comprehensiveness and low in cost; in the preparation process of the battery, the cellulose-containing solid electrolyte and the diaphragm are compounded to form a solid electrolyte-diaphragm compound with high mechanical strength and high thermal stability, so that the resistance of the battery to thermal runaway is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a solid electrolyte, a battery containing the solid electrolyte, and a preparation method thereof. Background Art

[0002] The irreversible thermal runaway of lithium batteries starts with a large-area internal short circuit caused by the dissolution of the diaphragm. The use of high-temperature resistant materials and diaphragms is an effective means to improve the safety of lithium batteries. Among them, cellulose materials have become effective composite materials for inhibiting the thermal shrinkage of diaphragms due to their low cost, high heat resistance, and high chemical stability. Xiong et al. successfully reduced the thermal shrinkage rate of PE diaphragms at 140°C to 19% by coating ethyl cellulose on the surface of polyethylene (PE) diaphragms (10.1016 / j.carbpol.2013.10.073); Jiangsu Housheng New Energy Technology Co., Ltd. prepared a cellulose-based diaphragm with improved air permeability, closed-cell temperature, heat shrinkage resistance, and electrolyte wettability by coating PE on a cellulose-based film (CN117766946A). Honeycomb Energy Technology Co., Ltd. has prepared a composite diaphragm with high safety and high electrolyte wettability by double electrospinning of cellulose and polymer on a base membrane, and the membrane rupture temperature has been increased from 150°C to above 250°C (CN117766945A).

[0003] However, cellulose materials have inherent defects as separator composite materials: first, the hydroxyl groups in its structure will increase the hygroscopicity of the separator; second, for advanced separators with functional coatings, such as LATP-coated separators, flame-retardant hydrotalcite-coated separators, and cage-type polysilsesquioxane-coated separators, additional cellulose coating will further increase the separator thickness and battery impedance, affecting the energy performance of lithium batteries. As a separator matrix, cellulose itself has shortcomings such as poor electrolyte wettability and inability to close pores, and needs to be coated with a polymer layer such as PVDF-HFP on its surface, which increases the overall cost of the battery. Summary of the invention

[0004] The object of the present invention is to provide a solid electrolyte, a battery containing the solid electrolyte and a preparation method thereof, so that the prepared solid electrolyte and battery have excellent heat resistance and electrical properties.

[0005] Technical solution:

[0006] In a first aspect, the present application provides a solid electrolyte:

[0007] A solid electrolyte is made from an electrolyte precursor through a heat-induced in-situ polymerization process; the electrolyte precursor includes cellulose, a polymer monomer, a lithium salt, a plasticizer, an additive and a thermal initiator; the polymer monomer contains at least one unsaturated double bond.

[0008] The electrolyte precursor of the solid electrolyte provided by the present invention fully infiltrates the diaphragm during the manufacturing process of the lithium battery, and then generates a diaphragm-electrolyte composite with high thermal stability by in-situ polymerization, thereby improving the thermal runaway safety of the battery without increasing the thickness of the diaphragm.

[0009] In terms of performance, the molecular cross-linked cellulose and polymer phases achieved through in-situ polymerization fully fill the pores inside the diaphragm, thereby simultaneously improving the heat resistance and wettability of the diaphragm.

[0010] In terms of cost, this preparation process does not require any additional treatment of the diaphragm. Low-cost cellulose, as a polymer material, can replace part of the polymer monomers in the precursor, thereby reducing the overall cost of the solid electrolyte.

[0011] The solid electrolyte of the present application plays a role similar to that of conventional electrolytes in conducting lithium ions, and is compounded with the diaphragm to improve the thermal stability of the diaphragm.

[0012] Furthermore, the proportion of cellulose in the solid electrolyte is 1.5-5%.

[0013] Furthermore, the proportion of the cellulose material in the solid electrolyte is 3.5%.

[0014] Furthermore, the mass ratio of the cellulose, polymer monomer, lithium salt, plasticizer and additive is (3-5): (1.5-5): (72.5-77.5): 5: 12.5; the initiator is 0.5% of the mass fraction of the polymer monomer.

[0015] Furthermore, the cellulose is one or more of methyl cellulose, cellulose acetate, cellulose acetate butyrate, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, cellulose triacetate, cellulose acetate butyrate, hydroxypropyl cellulose, diethylaminoethyl cellulose, bacterial cellulose, cellulose acetate butyrate, and ethyl cellulose.

[0016] In thermal runaway experiments, cellulose has higher mechanical strength and heat resistance than polymer phases and separators, which improves the overall heat resistance of the separator-electrolyte. As a polymer material, cellulose also absorbs and fixes the liquid components in the electrolyte.

[0017] Further, the polymer monomer is one or more of triethylene glycol dimethacrylate, ethylene glycol diacrylate, methoxypolyethylene glycol acrylate, (propylene glycol) methacrylate, (propylene glycol) dimethacrylate, ethylene glycol methyl ether methacrylate, ethylene glycol dimethacrylate, perfluoroalkylethyl methacrylate, 2-phenylethyl acrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, and pentaerythritol tetraacrylate.

[0018] Furthermore, the plasticizer is one or more of ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethyl acetate, methyl acetate, ethyl propionate, propyl acetate, and propyl propionate.

[0019] The polymer after in-situ polymerization has a high affinity with the liquid component in the electrolyte, and blocks the pores in the diaphragm by forming a uniform gel with the remaining components in the precursor, thereby improving its thermal stability; its technical feature is that the polymer monomer contains at least one unsaturated double bond.

[0020] The lithium salt acts as a carrier to conduct electric charge, and the lithium salt includes one or more salts commonly used in the field of lithium ion batteries, such as lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide), lithium bis(trifluoromethylsulfonylimide), etc. The present invention does not limit the type, content and ratio of the salt.

[0021] The plasticizer acts as a common solvent for cellulose and lithium salt, dissolving the lithium salt and forming a movable core-shell structure with lithium ions, thereby conducting charge. Its technical effects also include dissolving cellulose and making it uniformly dispersed in the electrolyte phase. Its technical feature is that the plasticizer includes one or more liquid plasticizers commonly used in the field of lithium ion batteries, and the present invention does not limit the type, content and proportion of the plasticizer.

[0022] The additive, as an interface film-forming agent, forms a stable passivation film on the surface of the positive and negative electrodes during the formation process to inhibit the side reaction of the electrolyte at the electrode interface; its technical feature is that the additive includes one or more additives commonly used in the field of lithium-ion batteries, and the present invention does not limit the type, content and proportion of the additive. The additive can be one or more additives commonly used in the field of lithium-ion batteries, such as fluoroethylene carbonate, vinylene carbonate, ethylene sulfite, 1,3-propane sultone, etc.

[0023] When the initiator is heated, it decomposes to generate free radicals, inducing the polymerization of polymer monomers, thereby achieving an in-situ polymerization curing effect; its technical feature is that the initiator includes one or more initiators commonly used in the field of lithium-ion batteries, and the present invention does not limit the type, content and proportion of the initiator.

[0024] In a second aspect, the present application provides a method for preparing a battery, comprising the following preparation steps:

[0025] S1 Negative electrode sheet preparation: Disperse the negative electrode active material, conductive agent, binder, and sodium carboxymethyl cellulose in water, and make a uniformly dispersed negative electrode slurry according to the slurry making process. Coat the negative electrode slurry on copper foil, bake, roll, cut, and punch to obtain the negative electrode sheet;

[0026] S2 positive electrode sheet preparation: the positive electrode active material, conductive agent and binder are dispersed in an organic solvent to prepare a uniformly dispersed positive electrode slurry; the positive electrode slurry is coated on an aluminum foil, baked, rolled, cut and punched to obtain a positive electrode sheet;

[0027] S3 dry cell assembly: stack the positive and negative electrode sheets prepared above using a separator to prepare a soft pack battery;

[0028] S4 battery preparation: In an inert gas atmosphere, the solid electrolyte precursor described in the present application is injected into a dry battery cell, the precursor is dissolve, and in-situ polymerization is carried out by thermal initiation to prepare a battery.

[0029] Furthermore, the mass ratio of the negative electrode active material, the conductive agent, the binder and sodium carboxymethyl cellulose is 97:1:1:1; the mass ratio of the positive electrode active material, the conductive agent and the binder is 96:2:2.

[0030] In a third aspect, the present application provides a battery, which is prepared using the battery preparation method of the present application.

[0031] Beneficial effects:

[0032] The innovation of the present invention is that by dissolving cellulose in a solid electrolyte precursor and uniformly compounding it with the diaphragm during in-situ polymerization, the heat shrinkage resistance of the diaphragm and the overall safety of the battery are improved; compared with the process of using cellulose on the diaphragm side to improve safety, the present invention does not require any additional treatment of the diaphragm, nor does it increase the thickness of the diaphragm. It is compatible with existing conventional diaphragms and diaphragms coated with advanced materials, and has comprehensive advantages in material cost, processing cost and battery performance; during the manufacturing process of the battery of the present application, the cellulose-containing solid electrolyte and the diaphragm are compounded to form a solid electrolyte-diaphragm composite with high mechanical strength and high thermal stability, thereby improving the battery's resistance to thermal runaway. DETAILED DESCRIPTION

[0033] In order to make the technical solution of the present invention clearer, the present invention is further described in detail with reference to specific embodiments.

[0034] Example 1

[0035] An electrolyte precursor, the preparation of which comprises the following steps:

[0036] Preparation of plasticizer: Control the moisture content in the glove box to be no more than 10 ppm, stir and mix ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1, and purify and remove impurities and water with molecular sieves to obtain the plasticizer.

[0037] Preparation of electrolyte precursor: In a glove box, ethyl cellulose, pentaerythritol tetraacrylate monomer, plasticizer, fluoroethylene carbonate, and lithium hexafluorophosphate are mixed in a mass ratio of 5:5:72.5:5:12.5, and stirred thoroughly until clarified. Azobisisobutyronitrile accounting for 0.5% of the monomer mass fraction is added as an initiator, and stirred again until clarified to obtain an electrolyte precursor; the electrolyte precursor can be cured into a cellulose-based high-safety solid electrolyte after heating.

[0038] Example 2

[0039] An electrolyte precursor, compared with Example 1, is different in that the mass ratio of each component in the electrolyte precursor is 4:5:73.5:5:12.5.

[0040] Example 3

[0041] An electrolyte precursor, compared with Example 1, is different in that the mass ratio of the components in the electrolyte precursor is 3.5:5:74:5:12.5.

[0042] Example 4

[0043] An electrolyte precursor, compared with Example 1, is different in that the mass ratio of each component in the electrolyte precursor is 3:5:74.5:5:12.5.

[0044] Example 5

[0045] An electrolyte precursor, compared with Example 1, is different in that the mass ratio of each component in the electrolyte precursor is 3.5:1.5:77.5:5:12.5.

[0046] Example 6

[0047] An electrolyte precursor, compared with Example 1, is different in that the mass ratio of each component in the electrolyte precursor is 3.5:2.5:76.5:5:12.5.

[0048] Comparative Example 1:

[0049] An electrolyte precursor, compared with Example 1, is different in that the electrolyte precursor is a mixture of a plasticizer, fluoroethylene carbonate and lithium hexafluorophosphate in a mass ratio of 82.5 / 5 / 12.5, and is free of cellulose, monomers and azobisisobutyronitrile.

[0050] Comparative Example 2:

[0051] An electrolyte precursor, compared with Example 1, is different in that the electrolyte precursor is composed of pentaerythritol tetraacrylate monomer, plasticizer, fluoroethylene carbonate, and lithium hexafluorophosphate mixed in a mass ratio of 5:77.5:5:12.5, and no cellulose is added.

[0052] Comparative Example 3:

[0053] An electrolyte precursor, compared with Example 1, is different in that the electrolyte precursor is prepared by mixing ethyl cellulose, a plasticizer, fluoroethylene carbonate, and lithium hexafluorophosphate in a mass ratio of 3.5:79:5:12.5, and no polymer monomer is added.

[0054] A battery is manufactured by the following method:

[0055] S1 preparation of negative electrode sheet: disperse the negative electrode active material (graphite), conductive agent (carbon black), binder (styrene-butadiene rubber), and sodium carboxymethyl cellulose in water (total solid content is 50wt%) at a mass ratio of 97:1:1:1, and prepare a uniformly dispersed negative electrode slurry according to the pulping process; coat the negative electrode slurry on copper foil, bake, roll, cut, and punch to obtain a negative electrode sheet.

[0056] Preparation of S2 positive electrode sheet: Disperse the positive electrode active material (LiNi0.8Co0.1Mn0.1O2), conductive agent (carbon black), and binder (polyvinylidene fluoride) in an appropriate amount of N-methylpyrrolidone (total solid content is 75wt%) at a mass ratio of 96:2:2, and prepare a uniformly dispersed positive electrode slurry according to the pulping process; coat the positive electrode slurry on aluminum foil, bake, roll, cut, and punch to obtain a positive electrode sheet.

[0057] S3 dry cell assembly: The positive and negative electrode sheets prepared above are stacked using a separator to prepare a soft-pack battery.

[0058] S4 battery is made by injecting a solid electrolyte precursor or electrolyte into a dry battery cell in a protective atmosphere with a moisture and oxygen content of no more than 10 ppm. After curing at 10 PSI, 38°C and 72 hours, a battery is prepared.

[0059] There are two types of separators, one is a LATP|PE|LATP structure with a thickness of 2+9+2=13μm; the other is an ethyl cellulose separator; the ethyl cellulose separator is prepared in the following way:

[0060] Ethyl cellulose was dissolved in tetrahydrofuran at a solid content of 10 wt %, and the obtained dispersion was coated on a PET foil with a doctor blade. After the solvent was evaporated at 60° C., an ethyl cellulose film with a thickness of 15 μm was obtained.

[0061] B01-B06 are used to represent different batteries, which are distinguished by the different separators and electrolyte precursors used. The specific correspondence between the battery, separator and electrolyte precursor and the electrical properties are shown in Table 2; the specific performance test fees of the solid electrolyte and battery are as follows:

[0062] Heat resistance test of solid electrolyte:

[0063] Performance 1: Heat resistance test

[0064] In this patent, an electrolyte-diaphragm composite is used to characterize the heat resistance of the solid electrolyte. The electrolyte-diaphragm composite is made by the following method: the moisture content in the glove box is controlled to be no more than 10ppm, and the positive electrode shell-stainless steel sheet-diaphragm-stainless steel sheet are assembled in sequence. After 200μL of excess electrolyte precursor is added to the battery, the negative electrode shell is assembled and pressed into a symmetrical battery. The battery is placed in a 38°C oven for 72 hours and then disassembled. The solid electrolyte-diaphragm composite between the stainless steel sheets is taken out, and its diameter is tested with a stainless steel ruler to be L1. The composite is stacked in a clean A4 paper, baked at 200°C for 1 hour, and then taken out and tested again with a stainless steel ruler to be L2. Thermal shrinkage rate ΔL = (1-L2 / L1) * 100%, and the relevant test results are shown in Table 1.

[0065] A01-A011 are used to represent different electrolyte-diaphragm composites, which are distinguished by the different diaphragms and electrolyte precursors used. The specific correspondence between the electrolyte-diaphragm composites and the diaphragms and electrolyte precursors is shown in the table, and the test results are shown in Table 1:

[0066] Table 1. Test results of heat resistance of solid electrolyte

[0067]

[0068] Comparing A05, A06, and A08, it can be seen that the LATP coated diaphragm itself can maintain good thermal stability at 200°C, which is caused by the surface coating of high heat-resistant ceramics. Although the low-melting-point PE base film melted at 200°C, the presence of the surface LATP diaphragm prevented the diaphragm from shrinking severely, so it would not cause a serious short circuit. However, after the diaphragm and electrolyte (A05) were compounded, the electrolyte significantly affected the thermal shrinkage of the diaphragm, and replacing the electrolyte with a solid electrolyte with higher mechanical strength could not effectively alleviate this phenomenon (A06). Comparing A06, A01 to A04, it can be seen that adding ethyl cellulose with high heat resistance (melting point>240°C) to the gel can effectively improve the heat resistance of the electrolyte-diaphragm composite when the cellulose ratio is 3.5% or above. Comparing A03, A08 to A10, it can be considered that under the premise of maintaining 3.5% of ethyl cellulose, the monomer ratio in the electrolyte precursor does not affect the thermal stability of the final electrolyte-diaphragm composite.

[0069] Comparing A06 and A011, it can be seen that compared with traditional ceramic diaphragms, ethyl cellulose itself has higher thermal stability, and the solid electrolyte composite product in the form of in-situ polymerization can maintain structural stability at 200°C.

[0070] Battery electrical performance test:

[0071] Electrical performance 1: 25℃ charging rate performance test

[0072] At 25℃ and 10PSI pressure, charge to 4.25V at 0.33C constant current, charge to 0.05C at 4.25V constant voltage, discharge to 2.8V at 0.33C constant current, and record the discharge capacity C0. After charging and discharging 3 times, charge to 4.25V at 3.0C constant current, and discharge to 2.8V at 0.33C constant current, and record the discharge capacity C1; 25℃ 3C charging rate = C0 / C1*100%. The relevant test results are shown in Table 2.

[0073] Electrical performance 2: 60℃ storage performance test

[0074] At 25℃ and 10PSI pressure, charge to 4.25V at 0.33C constant current, charge to 0.05C at 4.25V constant voltage, discharge to 2.8V at 0.33C constant current, record the discharge capacity C0, charge to 4.25V at 0.33C-0.05C constant current and constant voltage, store in a 60℃ oven for 30 days, discharge to 2.8V at 0.33C constant current, charge to 4.25V at 0.33C-0.05C constant current and constant voltage again, discharge to 2.8V at 0.33C constant current, repeat for three weeks, and record the final discharge capacity C1. 60℃ 30-day storage capacity recovery rate = C1 / C0*100%, related test results are shown in Table 2.

[0075] Electrical performance 3: 45℃ cycle performance test

[0076] At 45℃ and 10PSI pressure, charge to 4.25V at 1.0C constant current, charge to 0.05C at 4.25V constant voltage, discharge to 2.8V at 1.0C constant current, record the discharge capacity C0, repeat the above charge and discharge steps for 300 cycles, and record the final discharge capacity C1. 45℃ 300-cycle cycle retention rate = C1 / C0*100%. Related test results are shown in Table 2.

[0077] Table 2. Test results of the electrical performance of batteries B01-B06

[0078]

[0079]

[0080] Comparing the test data of B04 and B06, it can be seen that adding 3.5% ethyl cellulose to the electrolyte will cause a decrease in rate, storage performance and cycle stability. This is because cellulose introduces additional hydroxyl groups, causing the acidity of the electrolyte to increase. Comparing the test data of B04 and B05, it can be seen that the gel phase has lower ionic conductivity than the liquid phase, which affects the rate performance of the battery, but the gel state also inhibits the movement of the plasticizer, thereby limiting the side reactions and gas production at the internal interface of the battery, which is reflected in the improvement of storage stability and cycle stability. Comparing the test data of B01, B02, B03, B06, and B07, it can be seen that the presence of gel inhibits the negative effects of cellulose introducing hydroxyl groups on the electrolyte, which is reflected in higher high-temperature storage stability. However, the excessively high polymer phase ratio (B01, B03) also leads to a decrease in rate performance and cycle stability. Ethyl cellulose is directly used as a diaphragm, and its impedance is higher than that of conventional diaphragms, and the ratio of introduced hydroxyl groups is also higher. The solid-state battery prepared in this way has disadvantages in rate performance, high-temperature storage, and cycle performance. In contrast, in B02, gel and cellulose have the best synergy, and the corresponding battery has the best overall performance.

[0081] Battery safety test (heat resistance):

[0082] The battery in this patent is tested for heat resistance safety using the following method:

[0083] The battery using the electrolyte of Example 5, Comparative Example 1 and Comparative Example 2 was charged to 4.25V at 0.33C-0.05C constant current and constant voltage at 25°C and 10PSI pressure, and the pressure was maintained. The battery was placed in a 60°C oven and kept warm for 150 minutes. The temperature was then raised to 180°C at a rate of 5°C / min and kept warm for 1 hour, or the battery was taken out after cooling to below 50°C. The relevant test results are shown in Table 3.

[0084] Table 3. Heat resistance safety test results of batteries B02, B04, B05 and B06:

[0085] Battery Electrolyte Precursors Passed Post-test appearance B02 Example 5 yes No flatulence, no leakage B04 Comparative Example 1 no Spontaneous combustion B05 Comparative Example 2 no Spontaneous combustion B06 Comparative Example 3 no Serious leakage

[0086] It can be seen from the test data in Table 3 that the solid electrolyte (B04) or electrolyte (B02) without cellulose components cannot effectively suppress thermal runaway at 180°C after being compounded with the diaphragm, which is consistent with the heat resistance test results of the electrolyte-diaphragm composite. After the cellulose-dissolved electrolyte infiltrates the diaphragm, although the thermal stability of the diaphragm is improved, the uninhibited side reactions with the pole piece lead to serious gas production and eventual leakage. The solid electrolyte containing cellulose solves the problems of gas production and thermal shrinkage of the diaphragm at the same time, and ultimately greatly improves the safety of the battery.

[0087] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A solid electrolyte, characterized in that It is made from an electrolyte precursor through a heat-induced in-situ polymerization process; the electrolyte precursor includes cellulose, a polymer monomer, a lithium salt, a plasticizer, an additive and a thermal initiator; the polymer monomer contains at least one unsaturated double bond.

2. A solid electrolyte according to claim 1, characterized in that: The proportion of the cellulose in the solid electrolyte is 1.5-5%.

3. A solid electrolyte according to claim 2, characterized in that: The proportion of the cellulose material in the solid electrolyte is 3.5%.

4. A solid electrolyte according to claim 1, characterized in that: The mass ratio of the cellulose, polymer monomer, lithium salt, plasticizer and additive is (3-5): (1.5-5): (72.5-77.5): 5: 12.5; the initiator is 0.5% of the mass fraction of the polymer monomer.

5. A solid electrolyte according to claim 1, characterized in that: The cellulose is one or more of methyl cellulose, cellulose acetate, cellulose acetate butyrate, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, cellulose triacetate, cellulose acetate butyrate, hydroxypropyl cellulose, diethylaminoethyl cellulose, bacterial cellulose, cellulose acetate butyrate, and ethyl cellulose.

6. A solid electrolyte according to claim 1, characterized in that: The polymer monomer is one or more of triethylene glycol dimethacrylate, ethylene glycol diacrylate, methoxy polyethylene glycol acrylate, (propylene glycol) methacrylate, (propylene glycol) dimethacrylate, ethylene glycol methyl ether methacrylate, ethylene glycol dimethacrylate, perfluoroalkylethyl methacrylate, 2-phenylethyl acrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, and pentaerythritol tetraacrylate.

7. A solid electrolyte according to claim 1, characterized in that: The plasticizer is one or more of ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethyl acetate, methyl acetate, ethyl propionate, propyl acetate and propyl propionate.

8. A method for preparing a battery, characterized in that: The method comprises the following preparation steps: S1 Negative electrode sheet preparation: Disperse the negative electrode active material, conductive agent, binder, and sodium carboxymethyl cellulose in water, and make a uniformly dispersed negative electrode slurry according to the slurry making process; apply the negative electrode slurry on copper foil, bake, roll, cut, and punch to obtain a negative electrode sheet; S2 positive electrode sheet preparation: the positive electrode active material, conductive agent and binder are dispersed in an organic solvent to prepare a uniformly dispersed positive electrode slurry; the positive electrode slurry is coated on an aluminum foil, baked, rolled, cut and punched to obtain a positive electrode sheet; S3 dry cell assembly: stack the positive and negative electrode sheets prepared above using a separator to prepare a soft pack battery; The S4 battery is manufactured by injecting the solid electrolyte precursor described in any one of claims 1 to 7 into a dry battery cell in an inert gas atmosphere, and the electrolyte precursor is thermally initiated to undergo in-situ polymerization to prepare a battery.

9. A method for preparing a battery according to claim 8, characterized in that: The mass ratio of the negative electrode active material, the conductive agent, the binder and sodium carboxymethyl cellulose is 97:1:1:1; the mass ratio of the positive electrode active material, the conductive agent and the binder is 96:2:

2.

10. A battery prepared according to the method for preparing a battery according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Composite positive electrode capable of working at high voltage and preparation method thereof

    CN110676447A

  • Preparation method of polymer electrolyte taking cellulose as additive

    CN111490288A

  • Preparation method of polyethylene glycol diacrylate-based gel electrolyte

    CN111554974A

  • Novel gel electrolyte and lithium ion battery preparation method

    CN116093423A

  • Semi-solid battery and preparation method thereof

    CN116759639A

Cited By

  • Cellulose diacetate-based composite solid electrolyte as well as preparation method and application thereof

    CN120978189A

  • A cellulose diacetate-based composite solid electrolyte and a preparation method and application thereof

    CN120978189B

  • Composite solid electrolyte diaphragm, preparation method and all-solid-state battery

    CN121054967A

  • Composite solid electrolyte separator, method of preparation and all-solid-state battery

    CN121054967B